Drinking Water Purification with Ozone Process of Ujjain City - Khode, Sheetal; Srivastava, Alka; Dalal, Dr. Parag; Srivastava, Dr. J.K. (IJRDO-Journal of Applied Science, 2017)
Drinking water quality must be managed in such a way that has no adverse health effects areencountered. Such hazards are usually attributed to contamination. Disinfection of water andwastewater with oxidation appears to be a potential alternative to the use of chlorine as adisinfectant. Chlorine has the disadvantage of forming potentially toxic and carcinogenic byproducts,like as trihalomethanes and haloacetic acids. This concern, coupled with the facts thatgermicidal ozonation is effective in the inactivation of a variety of microorganisms and does notproduce undesirable by-products as a viable disinfectant for drinking water.This paper discusses the effect that ozone take in the contaminants present in the drinking waterand how it ozone reduce that contaminants, focus is on Ujjain.